Yeast isolates to inhibit blue mould and bitter rot of apples - Boyd-Wilson, K.S.H.; Glithero, N.; Ma, Q.; Alspach, P.A.; Walter, M. (New Zealand Plant Protection, 2006)
Yeast isolates (44) collected from New Zealand orchards were screened for their ability to inhibit lesion development of blue mould of apples caused by Penicillium spp and bitter rot of apples caused by Colletotrichum acutatum using a detached apple assay While 28 isolates reduced blue mould lesions significantly compared to the pathogen control only four of the 44 isolates reduced bitter rot lesion development significantly These four yeast isolates also reduced the lesion development of blue mould Increasing concentrations of selected yeasts decreased lesion size in a loglinear fashion Yeasts applied before the pathogen reduced the lesion size significantly better than when applied after the pathogen The best reduction in lesion development was achieved by live yeast cells washed and applied in sterile water without any nutrient supplements Yeast cell extracts did not result in reduced lesion development